Consumer protection and sustainable development: key green research areas - Paduszyńska, Marta; Kozar, Łukasz Jarosław (Ekonomia i Prawo. Economics and Law, 2024)
Motivation: Consumers are an important link in the socio-economic system. In the literature, there is a noticeable increase in interest on the part of researchers in shaping consumer attitudes and behaviour in various markets, including the issue of pro-environmental attitudes and behaviour. In the context of contemporary transformations and challenges of sustainable development, the importance of solutions aimed at providing consumers with adequate protection against a variety of unfair market practices misleading consumers on the issue of green products and services is growing. The motivation for undertaking this research was the need to highlight the complexity of green issues around consumer protection and, at the same time, to address them from a sustainability perspective. This can be an important step in discussing and setting further research directions in this area. Aim: The aim of this article is to identify key green research areas undertaken around consumer protection issues while addressing them from a sustainable development perspective. The implementation of this objective consisted of a literature review of the subject listed in the Scopus database and the Web of Science database. The methods adopted were a Structured Literature Review with original Q1-Q4 queries and a Classic Literature Review. Results: In economic reality, it can be observed that an increasing number of economic actors are offering products and services that are labelled green. They support the transformation of the current economy toward a green economy. However, the analyses show that consumers are increasingly confronted with the phenomenon of greenwashing. This requires the creation of new solutions to protect consumers against such unfair practices. The results of the considerations undertaken show the interdisciplinary character of the undertaken considerations around the issue of consumer protection in the field of greenwashing.